First-in-human phase 1 study of the arginase inhibitor INCB001158 alone or combined with pembrolizumab in patients with advanced or metastatic solid tumours - Michael Smith; Aung Naing; Todd Bauer; Kyriakos P Papadopoulos; Osama Rahma; Elena Garralda; Glenn J Hanna; Michael J Pishvaian; Xuejun Chen; Sven Gogov; Omar Saavedra; Howard Kallender; et al. (BMJ Oncology, 2024)
Objective The arginase inhibitor INCB001158 was evaluated for safety (primary endpoint) in locally advanced or metastatic solid tumours; pharmacokinetics, pharmacodynamics and efficacy were also assessed.Methods and analysis In this non-randomised, open-label, three-part phase 1 study, INCB001158 was orally administered two times per day as monotherapy or in combination with intravenous pembrolizumab 200 mg every 3 weeks. Dose expansion was conducted in tumour-type cohorts (with or without prior anti−PD-1/PD-L1 (programmed death protein 1/programmed death ligand 1) therapy).Results A total of 107 patients received INCB001158 50–150 mg two times per day as monotherapy, and 153 patients, including 6 with moderate renal impairment, received INCB001158 50–100 mg two times per day combined with pembrolizumab. INCB001158 exposure was similar between groups (median, 56 days (monotherapy); 84 days (combination)). 49 patients (45.8%) on monotherapy and 76 (51.7%) on combination therapy experienced grade ≥3 treatment-emergent adverse events (AEs). The most common INCB001158-related AEs were fatigue (n=10/107 (9.3%)) and nausea (n=10/107 (9.3%)) with monotherapy and diarrhoea (n=24/147 (16.3%)) and fatigue (n=22/147 (15.0%)) with combination therapy. The highest response rate was seen in the anti–PD-1/PD-L1–naive combination therapy group with head/neck squamous cell carcinoma (overall response rate, 19.2%; 4/26 partial responses, 1/26 complete response). Consistent with arginase inhibition activity, plasma arginine dose-dependently increased. Arginase 1 expression in the tumour microenvironment did not correlate with response.Conclusions INCB001158 was generally well tolerated. Response rates did not exceed background for given tumour types despite demonstrable pharmacodynamic activity. Overall, the limited antitumour activity of arginase inhibition observed suggests that the role of arginine depletion in cancer is multifaceted.Trial registration number NCT02903914.